INTERPRETATION OF JIHAD IN THE QUR’AN: CONTEXTUALIZATION Q.S. AL-BAQARAH (2): 190 PERSPECTIVE OF INDONESIAN MUFASSIR - Ruslan, Mohammad (Universitas Nurul Jadid, 2022)
The Qur’an is a source of knowledge that explains various aspects of life, including Jihad. Jihad is one of the orders of war for Muslims, which is defensive as a bulwark for Muslims, which lately Jihad is often misunderstood by the general public. Also, there are often movements of terrorism and radicalism in the name of Jihad, so it is necessary to research Jihad. This research aims to discover the concept of Jihad in the Q.S. Al-Baqarah (2): 190 from the perspective of M. Quraish Shihab, which samples are taken from various references from his work which interpret Jihad according to context. According to M. Qurasih Shihab, Q.S. Al-Baqarah (2): 190 explains that it is permissible to wage war during the war fī sabīlillah (in the way of Allah) to uphold the values of Belief in the One and Only God. The verse also explains the ethics and rules for conducting war, as well as guidance not to stand idly by and wait for the enemy to enter the area or threaten peace and harmony. The thinking method used in this study is the deductive method, namely collecting, analyzing and researching Jihad in the Q.S. Al-Baqarah (2): 190 in several kinds of literature, which is then narrowed down to the concept offered by M. Quraish Shihab in this verse which correlated with its implementation in the Indonesian context, therefore in analyzing the data, the author uses a framework built on theories developed in social sciences, linguistics, and scientific tools developed in interpretation studies. The results of this study indicate the concept of Jihad in the Q.S. Al-Baqarah (2): 190 from the perspective of M. Quraish Shihab, namely: 1). The war to uphold religious values. 2). War is a form of defence. 3). Prohibition of destroying facilities and infrastructure unrelated to war. Moreover, it can be implemented in the Indonesian context in several areas of Jihad, including Jihad in the social field, Jihad in the education sector, and Jihad in the economic field.